Management of infection and ocular complications in pediatric SJS/TEN-like acute graft-versus-host disease: a clinical case study and literature review - Yan, Huimin; Mo, Yunjun; Li, Yue; Li, Qian; Luo, Liping; Meng, Qing; Jia, Lei; Zhou, Lintao; Xiao, Lixia; Fu, Xiaoying (Frontiers in Immunology, 2025)
Acute graft-versus-host disease (aGVHD) with skin manifestations reminiscent of Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) is associated with poor outcomes. However, optimal management strategies to enhance quality of life in SJS/TEN-like aGVHD remain undefined. This study aims to investigate the management of complex infections and acute ocular injury in patients with SJS/TEN-like aGVHD following allogeneic hematopoietic stem cell transplantation. We conducted a comprehensive analysis of the treatment course for a patient with SJS/TEN-like aGVHD, complemented by a literature review on acute ocular complications and their management in aGVHD patients. A patient diagnosed with grade IV skin aGVHD received effective treatment for multidrug-resistant Stenotrophomonas maltophilia using minocycline, aztreonam, and ceftazidime-avibactam. Combination therapy with liposomal amphotericin B and voriconazole was efficacious against mixed fungal infections. Immunological assessments indicated reduced lymphocyte counts and increased myeloid-derived suppressor cells, with elevated CD4+ PD-1+ exhausted and memory cells, reflecting a complex interplay of immune hyperactivity and suppression. A literature review showed that although age, gender, and transplant circumstances were not associated with ocular symptoms, grade II+ cutaneous aGVHD emerged as a key risk factor for conjunctival involvement, characterized by exudation and pseudomembrane formation. Topical glucocorticoids, tacrolimus and cyclosporine eye drops were effective, necessitating regular pseudomembrane removal. Evaluating drug susceptibility and immune status is vital for formulating precise therapies. Early recognition and management of ocular symptoms in SJS/TEN-like aGVHD are essential to prevent irreversible damage.